Gradient methods with selection technique for the multiple-sets split feasibility problem. (1st February 2020) - Yao, Yonghong; Postolache, Mihai; Zhu, Zhichuan
ABSTRACT: In this paper, we present two new iterative algorithms for approximating a solution of the multiple-sets split feasibility problem. The suggested algorithms are based on the gradient method with selection technique. Weak and strong convergence theorems are demonstrated.